Whole-cell tumor vaccines desialylated to uncover tumor antigenic Gal/GalNAc epitopes elicit anti-tumor immunity - Jianmei Huang; Meiying Li; Bingjie Mei; Junyang Li; Yi Zhu; Qiaoshan Guo; Jianming Huang; Guonan Zhang (Journal of Translational Medicine, 2022)
Abstract Background Aberrant sialoglycans on the surface of tumor cells shield potential tumor antigen epitopes, escape recognition, and suppress activation of immunocytes. α2,3/α2,6Gal- and α2,6GalNAc (Gal/GalNAc)-linked sialic acid residues of sialoglycans could affect macrophage galactose-type lectins (MGL) mediated-antigen uptake and presentation and promote sialic acid-binding immunoglobulin-like lectins (Siglecs) mediated-immunosuppression. Desialylating sialoglycans on tumor cells could present tumor antigens with Gal/GalNAc residues and overcome glyco-immune checkpoints. Thus, we explored whether vaccination with desialylated whole-cell tumor vaccines (DWCTVs) triggers anti-tumor immunity in ovarian cancer (OC). Methods Sialic acid (Sia) and Gal/GalNAc residues on OC A2780, OVCAR3, and ID8 cells treated with α2-3 neuraminidase (α2-3NA) and α2-6NA, and Sigec-9 or Siglec-E and MGL on DCs pulsed with desialylated OC cells were identified using flow cytometry (FCM); RT-qPCR determined IFNG expression of T cells, TRBV was sequenced using Sanger sequencing and cytotoxicity of αβ T cells was measured with LDH assay; Anti-tumor immunity in vivo was validated via vaccination with desialylated whole-cell ID8 vaccine (ID8 DWCTVs). Results Gal/GalNAc but not Sia residues were significantly increased in the desialylated OC cells. α2-3NA-modified DWCTV increased MGL but decreased Siglec-9 or Siglec E expression on DCs. MGLbright/Siglec-9dim DCs significantly up-regulated IFNG expression and CD4/CD8 ratio of T cells and diversified the TCR repertoire of αβ T-cells that showed enhanced cytotoxic activity. Vaccination with α2-3NA-modified ID8 DWCTVs increased MGLbright/Siglec-Edim DCs in draining lymph nodes, limited tumor growth, and extended survival in tumor-challenged mice. Conclusion Desialylated tumor cell vaccine could promote anti-tumor immunity and provide a strategy for OC immunotherapy in a clinical setting.